2017
DOI: 10.1038/s41593-017-0010-3
|View full text |Cite
|
Sign up to set email alerts
|

Social stress induces neurovascular pathology promoting depression

Abstract: Studies suggest that heightened peripheral inflammation contributes to the pathogenesis of major depressive disorder. We investigated the effect of chronic social defeat stress, a mouse model of depression, on blood-brain barrier (BBB) permeability and infiltration of peripheral immune signals. We found reduced expression of endothelial cell tight junction protein claudin-5 (cldn5) and abnormal blood vessel morphology in nucleus accumbens (NAc) of stress-susceptible but not resilient mice. CLDN5 expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
707
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 715 publications
(756 citation statements)
references
References 51 publications
39
707
8
2
Order By: Relevance
“…ELS may also lead to greater permeability of the BBB (Kuvacheva et al, ), which allows more peripheral inflammatory cytokines and cells to access the CNS. Indeed, experimental animal models have shown that vulnerability to the behavioral effects of stress are linked to greater permeability in the BBB (Menard et al, ). Through these and other mechanisms, neuroinflammation during critical phases of development may alter functional circuits in the brain (Ganguly & Brenhouse, ) and have profound implications for several neurotransmitters, including glutamate, serotonin, and dopamine (Dooley et al, ; Miller, Haroon, Raison, & Felger, ).…”
Section: Discussionmentioning
confidence: 99%
“…ELS may also lead to greater permeability of the BBB (Kuvacheva et al, ), which allows more peripheral inflammatory cytokines and cells to access the CNS. Indeed, experimental animal models have shown that vulnerability to the behavioral effects of stress are linked to greater permeability in the BBB (Menard et al, ). Through these and other mechanisms, neuroinflammation during critical phases of development may alter functional circuits in the brain (Ganguly & Brenhouse, ) and have profound implications for several neurotransmitters, including glutamate, serotonin, and dopamine (Dooley et al, ; Miller, Haroon, Raison, & Felger, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to autoimmune disorders, recruitment of peripheral monocytes into the brain parenchyma has been recently shown to be directly responsible for anxiety like phenotypes in mice following periods of psychological stress (Wohleb et al, 2018, Wohleb et al, 2013). Some debate exists over whether recruited peripheral monocytes infiltrate the brain parenchyma and directly interact with neurons or remain the perivascular space, where they generate depressive phenotypes via the production of inflammatory cytokines that diffuse across the brain parenchyma (Menard et al, 2017). When further investigating the indispensable components of monocyte infiltration into the brain using models of experimental autoimmune encephalitis (EAE) and stress-induced anxiety, it was established in both that the recruitment and activation of peripheral monocytes was dependent upon either a functional NLRP3 inflammasome or the activity of NLRP3 activated cytokines.…”
Section: Nlrp3 Inflammasome Cytokines and Their Effectsmentioning
confidence: 99%
“…Neutrophil extravasation into the brain along with neurotoxic extracellular traps has been observed in post-mortem brains of AD patients (Zenaro et al, 2015), while expression of myeloperoxidase, a marker of neutrophil activation, was up-regulated in the plasma of patients with both MDD and AD (Tzikas et al, 2014;Vaccarino et al, 2008). Moreover, dendritic or macrophage monocytes have been shown to infiltrate the extravascular brain regions in models of stress-induced depression and in a Tg3578 AD model, contributing to behavioural impairments and seizure susceptibility but also facilitating Aβ clearance (El Khoury et al, 2007;Koronyo-Hamaoui et al, 2009;Menard et al, 2017;Wohleb, McKim, Sheridan, & Godbout, 2015). While T lymphocyte and polymorphonuclear infiltration is better characterized in AD and MDD, further experimental testing using genetic models (Lys-M GFP + , Menard et al, 2017) can help to understand role and effects of monocyte trafficking in these disorders.…”
Section: Leukocyte Infiltration and T Lymphocyte Immunophenotypesmentioning
confidence: 99%
“…Moreover, dendritic or macrophage monocytes have been shown to infiltrate the extravascular brain regions in models of stress-induced depression and in a Tg3578 AD model, contributing to behavioural impairments and seizure susceptibility but also facilitating Aβ clearance (El Khoury et al, 2007;Koronyo-Hamaoui et al, 2009;Menard et al, 2017;Wohleb, McKim, Sheridan, & Godbout, 2015). While T lymphocyte and polymorphonuclear infiltration is better characterized in AD and MDD, further experimental testing using genetic models (Lys-M GFP + , Menard et al, 2017) can help to understand role and effects of monocyte trafficking in these disorders.…”
Section: Leukocyte Infiltration and T Lymphocyte Immunophenotypesmentioning
confidence: 99%